Maximum power point tracking CMOS circuit to connect a solar cell into a solid-state battery - Gonçalves, L. M. (2015)
This paper presents a Maximum Power Point Tracking (MPPT) circuit in CMOS technology for integration into an energy harvesting solution, comprising a solid-state thin-film lithium battery fabricated in the back side of a plastic solar cell. The MPPT CMOS circuit is required in the energy transfer process from the solar cell to the battery. The MPPT circuit was designed in the 0.7 µm CMOS process from on semiconductor (former AMIS, Alcatel-Mietec). The pulse width modulation (PWM) gate control of the DC-DC step-up converter is obtained only with analog circuits, which are composed by rail-to-rail operational amplifiers, analog multipliers and a ring oscillator. The ripple correlation control algorithm is used in the implementation of the analog MPPT circuit. This is a dynamically rapid method (e.g., 5 ms step response was measured) where the inevitable ripple of the inductor current of the DC-DC converter is analyzed and used to adjust the set-point of the same DC-DC converter. The full energy harvesting is also described in this paper.